2017
DOI: 10.1002/dev.21520
|View full text |Cite
|
Sign up to set email alerts
|

The mobile conjugate reinforcement paradigm in a lab setting

Abstract: The mobile conjugate reinforcement task was administered to 4-month-old infants in a lab rather than a home setting where it is usually administered. Learning and retention patterns were comparable to those of infants tested in their homes, suggesting flexibility in where this task can be administered. These results pave the way for this task to be used with a broader range of infants for whom home visits are not practical or convenient (e.g., infants in child care). Developmental research conducted with a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Descriptive statistics for the Bayley-III and mobile conjugate reinforcement paradigm are presented in Table 2 . The infants in this study demonstrated typical patterns of learning and memory performance on the mobile conjugate reinforcement paradigm (see also [ 40 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive statistics for the Bayley-III and mobile conjugate reinforcement paradigm are presented in Table 2 . The infants in this study demonstrated typical patterns of learning and memory performance on the mobile conjugate reinforcement paradigm (see also [ 40 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Learning and Memory At 4-months postpartum, mothers brought their infants to the lab on two consecutive days for participation in the mobile conjugate reinforcement paradigm [ 31 , 40 ] ( S1 Text ). After placing infants in a specially set up crib, each videotaped 15-min session began with a 3-min non-reinforcement phase (baseline), followed by a 9-min reinforcement phase (three 3-min learning blocks), and a final 3-min non-reinforcement phase (immediate retention).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…See Cuevas, Learmonth, & Rovee-Collier (2016) for a recent study of extinction conducted in the home. Fortunately, there is empirical evidence that home versus lab sessions yield comparable data (Merz et al, 2017). Control of time between sessions may be more easily accomplished if sessions are conducted at home.…”
Section: Discussionmentioning
confidence: 99%
“…See Cuevas, Learmonth, and Rovee-Collier (2016) for a recent study of extinction conducted in the home. Fortunately, there is empirical evidence that home versus lab sessions yield comparable data (Merz et al, 2017).…”
Section: Number Of Expressionsmentioning
confidence: 99%